All solid state stretchable carbon nanotube based supercapacitors with controllable output voltage. (December 2020) - Perez-Gonzalez, R.; Peng, Z.; Camacho, D.; Oliva, A.I.; Pei, Q.; Zakhidov, A.; Encinas, A.; Oliva, J.
Highlights: Stretchable supercapacitors were fabricated with silicon elastomers and CNT sheets. The maximum capacitance observed was 1328 F/g at 50% strain. The output voltage changed from 1.05 to 0.32 V after stretching the devices from 0 to 100%. The carboxylic groups and oxygen vacancies served as redox center for the storage of charge. Abstract: This work reports the electrochemical properties of stretchable supercapacitors fabricated with carbon nanotubes (CNTs) sheets as electrodes. According to the SEM images of the electrodes, the CNTs look like interconnected wires oriented in one direction. The electrochemical analysis indicated that the devices subjected from 0 to 150% strain decreased their capacitance from 712.2 to 88.4 F/g. Interestingly, the device stretched 525 times at 50% strain had a capacitance of 1328.3 F/g, which is one of the highest capacitance values reported so far for stretchable supercapacitors. The cycling voltammetry curves of the stretched devices showed redox peaks, suggesting that these devices store charge by Faradaic reactions. The presence of redox centers (carboxylic groups and oxygen vacancies) was confirmed by Fourier transform infrared spectroscopy, optical absorbance measurements, and X-ray photoelectron spectroscopy measurements. The galvanostatic charge/discharge curves showed the presence of two components: capacitive (discharge with exponential decay) and battery-type (stable output voltage). This output voltage was controlled with the strain %, since values of 1.05 V, 0.72 V, and 0.32 V were obtained for 0, 50, and 100% strain, respectively. The high capacitance and stable voltage demonstrated by the devices suggest that they could be used as energy sources in wearable/portable applications. Graphical abstract: Image, graphical abstract